A cluster randomised controlled trial to evaluate the impact of a gender transformative intervention on intimate partner violence against women in newly formed neighbourhood groups in Tanzania. Issue 7 (23rd July 2021) - Harvey, Sheila; Abramsky, Tanya; Mshana, Gerry; Hansen, Christian Holm; Mtolela, Grace J; Madaha, Flora; Hashim, Ramadhan; Kapinga, Imma; Watts, Charlotte; Lees, Shelley; Kapiga, Saidi
Abstract : Introduction: Violence against women is a global public health concern; around a quarter of women will experience intimate partner physical or sexual violence during their lifetime. We assessed the impact of a gender transformative intervention for women designed to prevent intimate partner violence (IPV). Methods: We conducted a cluster randomised controlled trial in Mwanza city, Tanzania, among women in newly formed neighbourhood groups to evaluate a 10-session participatory intervention that aims to empower women, prevent IPV and promote healthy relationships. Following a baseline interview, groups were randomly assigned (1:1 ratio) to the intervention or control arm. An intention-to-treat analysis was conducted to assess the impact of the intervention on the main outcomes, assessed 24 months postintervention. These included past-year physical IPV and sexual IPV (primary); past-year emotional abuse; and acceptability and tolerance of IPV. Results: Between September 2015 and February 2017, 1265 women were recruited in 66 neighbourhoods and randomly allocated to intervention (n=627 women in 33 neighbourhoods) or control (n=638 women in 33 neighbourhoods). Assessment of outcomes was completed for 551 (88%) intervention and 575 (90%) control women. Among intervention women, 113 (21%) reported physical IPV compared with 117 (20%) control women (adjusted OR (aOR) 0.98, 95% CI 0.72 to 1.33, p=0.892), and 109 (20%) intervention women reported sexual IPV compared with 121 (21%) control women (aOR 0.98, 95% CI 0.72 to 1.32, p=0.881). Intervention women reported less emotional abuse (aOR 0.74, 95% CI 0.56 to 0.98, p=0.035), and were less likely to express attitudes accepting of IPV (aOR 0.49, 95% CI 0.36 to 0.66, p<0.001), and beliefs that IPV is a private matter (aOR 0.54, 95% CI 0.38 to 0.78, p=0.001), or should be tolerated (aOR 0.48, 95% CI 0.34 to 0.66, p<0.001). Conclusion: These results indicate that the intervention was effective in reducing emotional abuse and positively impacting attitudes and beliefs condoning IPV, but was not sufficient to reduce physical or sexual IPV. Trial registration number: NCT02592252 .